Stimulus uncertainty affects perception in human echolocation: timing, level, and spectrum - Norman, LJ; Thaler, L (American Psychological Association, 2020)
The human brain may use recent sensory experience to create sensory templates that are then compared to incoming sensory input, that is, “knowing what to listen for.” This can lead to greater perceptual sensitivity, as long as the relevant properties of the target stimulus can be reliably estimated from past sensory experiences. Echolocation is an auditory skill probably best understood in bats, but humans can also echolocate. Here we investigated for the first time whether echolocation in humans involves the use of sensory templates derived from recent sensory experiences. Our results showed that when there was certainty in the acoustic properties of the echo relative to the emission, either in temporal onset, spectral content or level, people detected the echo more accurately than when there was uncertainty. In addition, we found that people were more accurate when the emission’s spectral content was certain but, surprisingly, not when either its level or temporal onset was certain. Importantly, the lack of an effect of temporal onset of the emission is counter to that found previously for tasks using nonecholocation sounds, suggesting that the underlying mechanisms might be different for echolocation and nonecholocation sounds. Importantly, the effects of stimulus certainty were no different for people with and without experience in echolocation, suggesting that stimulus-specific sensory templates can be used in a skill that people have never used before. From an applied perspective our results suggest that echolocation instruction should encourage users to make clicks that are similar to one another in their spectral content.